2016
DOI: 10.1021/acsami.6b12655
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinarily Durable Graphdiyne-Supported Electrocatalyst with High Activity for Hydrogen Production at All Values of pH

Abstract: We have used a scalable and inexpensive method to prepare a catalyst comprising graphdiyne nanosheet-supported cobalt nanoparticles wrapped by N-doped carbon (CoNC/GD); this unprecedentedly durable electrocatalyst mediated the hydrogen evolution reaction (HER) with highly catalytic activity over all values of pH. The durability of the CoNC/GD structure was evidenced by the catalytic performance being preserved over 36 000, 38 000, and 9000 cycles under basic, acidic, and neutral conditions, respectively-behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 69 publications
0
69
0
Order By: Relevance
“…Furthermore, Xue et al. reported that the N‐doped carbon‐wrapped GD nanosheet exhibited highly catalytic activity at all values of pH in electrocatalysis for the hydrogen evolution reaction . In addition, GD electrode applied to dye‐sensitized solar cells with the participation of Pt nanoparticles have also been reported by Ren et al.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, Xue et al. reported that the N‐doped carbon‐wrapped GD nanosheet exhibited highly catalytic activity at all values of pH in electrocatalysis for the hydrogen evolution reaction . In addition, GD electrode applied to dye‐sensitized solar cells with the participation of Pt nanoparticles have also been reported by Ren et al.…”
Section: Introductionmentioning
confidence: 98%
“…Superior to conventional carbon materials, a new carbon allotrope, GDY, featuring a single layer of sp‐ and sp 2 ‐hybridized carbon network, has been first synthesized by our group, predicted to be the most stable carbon allotrope, and demonstrated excellent catalytic performances, because of the rich pi bonds and large cavity structure . Owing to its unique electronic properties, graphdiyne possesses the natural band gap (0.47 or 1.12 eV, by two different methods), the intrinsic charge carrier mobility of graphdiyne (2 × 10 5 cm 2 V −1 s −1 ) which is higher than graphene and single‐wall carbon nanotubes (7.9 × 10 4 cm 2 V −1 s −1 ), and the silicon‐like electronic conductivity (2.56 × 10 −1 S m −1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon materials with high surface‐to‐volume ratio, predominant electroconductivity, and high endurance are better choices to support nanoparticles, [ 96 ] while the limited cycle life of such materials is a great challenge. [ 97 ]…”
Section: Gdy Supported Electrocatalysts For Energy Conversionmentioning
confidence: 99%
“…In 2016, Yang and co‐workers developed a scalable and inexpensive way to fabricate GDY‐supported Co nanoparticles (NPs) wrapped by N‐doped carbon (CoNC/GDY) as an excellent electrocatalyst for HER. [ 97 ] Previous study reported that the strong chemical adsorption between transition metals (such as Co) and alkyne rings of GDY was beneficial for depositing Co NPs on GDY surface. [ 99 ] In addition, this strong interaction resulted in the faster electron migration from Co NPs to GDY, which enriched the electron density of GDY and thereby boosted electrocatalytic performance.…”
Section: Gdy Supported Electrocatalysts For Energy Conversionmentioning
confidence: 99%
See 1 more Smart Citation